Catecholamines and the effects of exercise, training and gender - Zouhal, H. M; Jacob, C.; Delamarche, P.; Gratas-Delamarche, A. (Sports Medicine, 2008)
Stress hormones, adrenaline (epinephrine) and noradrenaline (norepinephrine), are responsible for many adaptations both at rest and during exercise. Since their discovery, thousands of studies have focused on these two catecholamines and their importance in many adaptive processes to different stressors such as exercise, hypoglycaemia, hypoxia and heat exposure, and these studies are now well acknowledged. In fact, since adrenaline and noradrenaline are the main hormones whose concentrations increase markedly during exercise, many researchers have worked on the effect of exercise on these amines and reported 1.5 to >20 times basal concentrations depending on exercise characteristics (e.g. duration and intensity). Similarly, several studies have shown that adrenaline and noradrenaline are involved in cardiovascular and respiratory adjustments and in substrate mobilization and utilization. Thus, many studies have focused on physical training and gender effects on catecholamine response to exercise in an effort to verify if significant differences in catecholamine responses to exercise could be partly responsible for the different performances observed between trained and untrained subjects and/or men and women. In fact, previous studies conducted in men have used different types of exercise to compare trained and untrained subjects in response to exercise at the same absolute or relative intensity. Their results were conflicting for a while.